Design and implementation of solar heater system - Redowan, Mesbah; Sami, Tasnim Muntasir; Islam, Aynul (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016. Cataloged from PDF version of thesis report. Includes bibliographical references (page 41). Overly populated and developing countries, such as our country Bangladesh is facing energy resources scarcity over the last few decades. Specially, the rural areas in Bangladesh which covers at least 50 % of our land suffers without electricity and the attempt to expand the grid system is incapable for the shortage of capacity. With the innovation of technology and high popularity of usage of renewable energy, the accessibility of electricity is present for all. Our aim is to design a project, which is the development of solar powered electric heater replacing the electric, or gas powered equipment. This allows the heater to be charged during the day by storing solar energy and be used during normal time. The future prospective is to bring along this success project to the commercial area and encourage investors to invest in this project and make it more popular among common people for household purposes. Mesbah Redowan Tasnim Muntasir Sami Aynul Islam B. Electrical and Electronic Engineering